2002
DOI: 10.1111/1540-6040.00031
|View full text |Cite
|
Sign up to set email alerts
|

Are Virtual Communities True Communities? Examining the Environments and Elements of Community

Abstract: Critiques of modern societies often cite the loss of community as a result of weak connections with local places and changing modes of social interactions. We will argue that both the loss of community and attempts to regain community can be understood as a series of debates progressing from one environment to another. Specifically, community was seen as being lost from its original environment, the local place, typically a village or a residential neighborhood. Then came the claim that community could be rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 37 publications
(52 reference statements)
1
56
0
1
Order By: Relevance
“…Driskell and Lyon [7] observed that it seems we never cease to pine for the tightknit communities putatively found in the small villages of Europe in the nineteenth century. Such villages were the inspiration for Tönnies's concept of Gemeinschaft-the intimate, close relations of a group of people who know one another well and share history and tradition [29].…”
Section: Discussion 71 a Multiplicity Of Interleaved Collaborationsmentioning
confidence: 97%
See 4 more Smart Citations
“…Driskell and Lyon [7] observed that it seems we never cease to pine for the tightknit communities putatively found in the small villages of Europe in the nineteenth century. Such villages were the inspiration for Tönnies's concept of Gemeinschaft-the intimate, close relations of a group of people who know one another well and share history and tradition [29].…”
Section: Discussion 71 a Multiplicity Of Interleaved Collaborationsmentioning
confidence: 97%
“…Such villages were the inspiration for Tönnies's concept of Gemeinschaft-the intimate, close relations of a group of people who know one another well and share history and tradition [29]. But MMOGs provide an occasion to reflect on whether such communities should be the gold standard [7]. While Gemeinschaft-style social groups provide deep, supportive bonds, such bonds can be constraining as well as fulfilling.…”
Section: Discussion 71 a Multiplicity Of Interleaved Collaborationsmentioning
confidence: 99%
See 3 more Smart Citations